2016
DOI: 10.11604/pamj.2016.23.128.8756
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hepatitis B virus infection in nigerian children prior to vaccine introduction into the national programme onimmunization schedule

Abstract: IntroductionHepatitis B virus infection is a major global health problem of public health importance. In a bid to control the infection, the Nigerian government in 2004 introduced hepatitis B vaccine into the National Program on Immunization. There are no studies on the prevalence of hepatitis B in adolescent prior to 2004. The study was aimed at determining the seroprevalence and predictors of viral Hepatitis B in Nigerian children aged 11-19 years.MethodsA cross sectional analytical study was conducted in Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 15 publications
4
48
3
Order By: Relevance
“…Studies in other parts of the world have demonstrated increasing 'a' determinant mutations over time, likely related to the expansion of hepatitis B vaccination [45]. In Nigeria, the hepatitis B vaccine was introduced in 1995, however not widely available until 2004 [46,47]. Patients in this study were all born prior to 2004, although vaccination history was not available in our study patients.…”
Section: Discussionmentioning
confidence: 89%
“…Studies in other parts of the world have demonstrated increasing 'a' determinant mutations over time, likely related to the expansion of hepatitis B vaccination [45]. In Nigeria, the hepatitis B vaccine was introduced in 1995, however not widely available until 2004 [46,47]. Patients in this study were all born prior to 2004, although vaccination history was not available in our study patients.…”
Section: Discussionmentioning
confidence: 89%
“…Sub-Saharan Africa is reported to have the highest burden of HBV and HCV infection in the world [1,2]. As a result of shared routes of transmission, co-infection of HCV and HBV is common among human immunodeficiency virus (HIV)-infected patients [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For comparing two proportions, the sample size formula used was n = (Zα/2+Zβ)2 * (p1(1-p1)+p2(1-p2)) / (p1-p2)2, where n is the sample size for a proportion, Zα/2 is the critical value of the Normal distribution at α/2 (for a confidence level of 95%, α is 0.05 and the critical value is 1.96), Zβ is the critical value of the Normal distribution at β (for a power of 80%, β is 0.2 and the critical value is 0.84) and p1 and p2 are the expected sample proportions of the two groups. For detecting a difference between two proportions, p1 was taken as 0.3 and p2 as 0.2 (Ikobah et al, 2016). Imputing values, n = (1.96+ 0.84)2 * (0.…”
Section: Methodsmentioning
confidence: 99%
“…1.2%. A 2014 study among Nigerian children 11-19 years found a sex specific prevalence of 0.8% for males and 1.8% for females and a prevalence rate of 1.2% (Ikobah et al, 2016).…”
Section: Introductionmentioning
confidence: 98%